Implementation of the Lagrange-Galerkin methods for the incompressible Navier-Stokes equations - Buscaglia, Gustavo C.; Dari, Enzo A. (Comisión Nacional de Energía Atómica; Argentina)
Fil: Buscaglia, Gustavo C. Comisión Nacional de Energía Atómica; Argentina